Influence of clinical and laboratory variables on faecal antigen ELISA results in dogs with canine parvovirus infection. Issue 3 (June 2015) - Proksch, A.L.; Unterer, S.; Speck, S.; Truyen, U.; Hartmann, K.
Highlights: False negative faecal antigen ELISA results are frequent for canine parvovirus (CPV). The main reason for a false negative faecal antigen ELISA is a low virus load. Clinical signs are similar in ELISA-positive and -negative dogs. Clinical outcome is similar in ELISA-positive and -negative dogs. Abstract: False negative faecal canine parvovirus (CPV) antigen ELISA results in dogs with CPV infection are common, but the factors that lead to these false negative results are still unknown. The aim of this study was to investigate whether dogs with a false negative faecal CPV antigen ELISA result have milder clinical signs and laboratory changes, a lower faecal virus load, higher faecal and serum CPV antibody titres and a faster recovery than dogs with a positive result. Eighty dogs with CPV infection, confirmed by the presence of clinical signs and a positive faecal CPV polymerase chain reaction (PCR), were assigned to two groups according to their faecal antigen ELISA result. Time until presentation, severity of symptoms, laboratory parameters, faecal virus load, faecal and serum antibody titres, and CPV sequencing data were compared between both groups. In 38/80 dogs that were hospitalised until recovery, the time to recovery, mortality, and the course of the disease were compared between dogs with positive and negative faecal antigen ELISA results. Of the 80 dogs included, 41 (51.3%) had a false negative faecal antigen ELISA result. ELISA-negative dogs had a significantly shorter time until presentation, lower frequency of defaecation, lower faecal virus load, and higher serum antibody concentrations than ELISA-positive dogs. Laboratory changes, CPV shedding, and outcomes were not associated with faecal antigen ELISA results. In conclusion, low faecal CPV load and antibodies binding to CPV antigen in faeces are likely to be important reasons for false negative faecal antigen ELISA results. Dogs with clinical signs of CPV infection should be retested by faecal PCR.